Affirming, intersectional spaces & positive religious coping: evidence-based strategies to improve the mental health of LGBTQ-identifying Muslims. Issue 1 (2nd January 2022) - Askari, Adnan S.; Doolittle, Benjamin
ABSTRACT: The interplay between Islam, sexuality, and mental health is complex. In large population studies, religiosity is associated with positive mental health outcomes. However, the data among LGBTQ populations is mixed. Structural, interpersonal, and individual forms of religious trauma may adversely affect the mental health of queer people in religious households, but robust social support can remedy these effects. In particular, the dual-identities of LGBTQ-identifying Muslims complicate their relationships with both religious and queer communities. Here, we present models of LGBTQ-inclusive Muslim spaces as intersectional pathways to positive mental health outcomes, simultaneously offering networks of social support and opportunities to engage with healthy religious coping mechanisms.